Pengendalian Intern Pelunasan Gadai pada PT. Pegadaian (Persero) Unit Pembantu Cabang (UPC) Jenggawah Kabupaten Jember - Candra Dewi, Monika Oktaria; Lestari, Hari Budi; Wiguna, Ardhitya Alam (ACCOUNT (Journal of Accounting and Finance), 2023)
This research aims to describe the internal control of pawn settlement at PT. Pegadaian (Persero) Jenggawah Branch Supporting Unit (UPC), Jember Regency. The method used in this research is descriptive qualitative. Data collection techniques were carried out using observation, documentation, literature review and interview methods. Then the findings were analyzed by comparing the results of the research with the previously existing theories related to internal control of mortgage settlement. The results of the study show that the internal control of mortgage settlement at PT. Pegadaian (Persero) Jenggawah Branch Support Unit (UPC) in Jember Regency is generally according to theory. From the 4 (four) elements that serve as benchmarks for the suitability of internal control for repayment of pawns based on theory, there is only 1(one) element that is not appropriate, namely the element of related functions. Information regarding credit can be added for further research.